2009
DOI: 10.1007/s00467-009-1301-z
|View full text |Cite
|
Sign up to set email alerts
|

Final height of adults with childhood-onset steroid-responsive idiopathic nephrotic syndrome

Abstract: The aim of this study was to evaluate the final stature of adults with childhood-onset steroid-responsive idiopathic nephrotic syndrome (INS) and the influence of disease-related issues on the achievement of their target heights. We analyzed 60 (41 male) patients and/or their records, with a minimum age of 19 years or at a Tanner's pubertal stage 4 for boys or status postmenarche for girls, and normal glomerular filtration rate. Mean age at first and last consultation was 5.3+/-2.4 years and 20.5+/-3.1 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Although this study was not designed to assess a causal relationship, this temporary effect corresponds with previous retrospective studies that describe a dose-dependent effect of corticosteroids on growth in children with NS. [27][28][29] It is unclear why baseline height SD scores were relatively low in our study population. A similar observation was reported in the work by Schärer et al, 30 whereas others described normal height SD scores at diagnosis of NS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this study was not designed to assess a causal relationship, this temporary effect corresponds with previous retrospective studies that describe a dose-dependent effect of corticosteroids on growth in children with NS. [27][28][29] It is unclear why baseline height SD scores were relatively low in our study population. A similar observation was reported in the work by Schärer et al, 30 whereas others described normal height SD scores at diagnosis of NS.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation was reported in the work by Schärer et al, 30 whereas others described normal height SD scores at diagnosis of NS. 27 In countries where a 2-month prednisolone regimen is applied for the first episode of NS, children who do not achieve remission within 4 weeks of daily prednisolone are generally characterized as steroid-resistant. Steroid resistance is associated with increased risk of renal failure and entails more aggressive immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Donatti and Koch measured the final height of 60 adults with childhood‐onset steroid‐sensitive NS and steroid‐dependent NS for a mean follow‐up period of 15.1 years. They found that the final height Z‐score only correlated with the initial and target height and reported that NS‐related issues did not prevent the patients reaching their predicted target height . In contrast, Emma et al followed up 42 children with steroid‐dependent and frequently relapsing NS for an average of 11.7 average years and showed that they lost 0.7 standard deviation (SD) of their target height and that the mean duration and average cumulative dose of steroid treatment was a predictor of poor growth.…”
Section: Growth and Heightmentioning
confidence: 99%
“…Subsequently, their later study evaluated the final height of 60 patients from their previous group and found that cumulative doses, treatment time and the age when they discontinued steroids did not influence their final height Z‐score. This study did not confirm their previous findings . In their study, the main determinants of the final height score were the initial Z‐ score and target height.…”
Section: Growth and Heightmentioning
confidence: 99%
See 1 more Smart Citation